Loss of Fbxw7 in Sertoli cells impairs testis development and causes infertility in mice. Issue 4 (28th December 2019) - Zhang, Hanbin; Chen, Feilong; Dong, Heling; Xie, Minyu; Zhang, Huan; Chen, Yan; liu, Hong; Bai, Xiaochun; Li, Xuemei; Chen, Zhenguo
Abstract: F-box and WD-40 domain protein 7 (Fbxw7) is a component of the Skp1-Cdc53/Cullin-F-box-protein complex (SCF/β-TrCP), which is an E3 ubiquitin ligase that mediates protein degradation. This complex has recently been shown to negatively regulate spermatogonial stem cell self-renewal; however, its roles in Sertoli cell (SC) proliferation, differentiation, and function remain to be established. In this study, we generated conditional mutant mice with SC-specific deletion of Fbxw7 via the Cre-loxP system. Fbxw7 deficiency in SCs impaired testis development, which is characterized by age-dependent tubular atrophy, excessive germ cell loss, and spermatogenic arrest, and the mutant males were infertile at 7 months old. Fbxw7 ablation also compromised cytoskeletal organization and cell polarity of SCs, as well as integrity of the blood-testis barrier. In addition, the transcript levels of cell markers for germ cells, Leydig cells, and SCs were significantly decreased in Fbxw7 mutant mice. Importantly, protein levels of GATA-4, a transcription factor that plays a crucial role in SC maturation and testis development, were progressively decreased in control SCs after postnatal day 14, whereas levels were aberrantly elevated in Fbxw7 -deleted SCs. Interestingly, the Gata-4 messenger RNA levels remained stable following Fbxw7 deletion. Fbxw7 silencing in SCs also induced progressive Leydig cell inefficiency and testosterone insufficiency. Collectively, these results demonstrate that Fbxw7 expression is required for SC maturation and function, potentially through degradation of GATA-4, to support pubertal testis development and spermatogenesis. Abstract : Fbxw7 is essential for pubertal testis development and spermatogenesis by regulating SC maturation and function, potentially through degradation of GATA-4.